1997
DOI: 10.1097/00000539-199710000-00037
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of General Anesthesia and Surgery on Basal and Interferon Stimulated Natural Killer Cell Activity of Humans

Abstract: Natural killer cells can kill cancer cells and virally infected cells. This study shows that surgery with general anesthesia leads to decreased natural killer cell activity as assessed int he laboratory. This decreased natural killer cell activity may lead to infection or tumor dissemination. NK activity can be restored to presurgery levels by treating isolated NK cells with interferon-alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
2
14
0
1
Order By: Relevance
“…This finding is supported by results of a previous investigation [5] in which investigators found no change in the lymphocyte ratio. Furthermore, the number of NK cells was constant in the present study, although the overall number of lymphocytes decreased in response to anesthesia.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding is supported by results of a previous investigation [5] in which investigators found no change in the lymphocyte ratio. Furthermore, the number of NK cells was constant in the present study, although the overall number of lymphocytes decreased in response to anesthesia.…”
Section: Discussionsupporting
confidence: 88%
“…Second, an experiment in mice revealed that interferon enhancement of NK activity was not detectable after mice were exposed to isoflurane [7]. In addition, it has been reported that NK activity decreases and that the reactivity between NK cells and interferon-γ is suppressed after anesthesia in humans [5]. Third, there may be a direct action of isoflurane on lymphocytes, because a decrease in NK cytotoxic activity has been reported in an ex vivo experiment in which human lymphocytes were exposed to isoflurane [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Im Tierexperiment konnte eine halothan-oder isofluraninduzierte Suppression der NK-Zellen trotz Zusatz immunstimulierender Faktoren nicht aufgehoben werden [56]. Ähnliche Ergebnisse wurden in perioperativen Patientenstudien bei Verwendung von Isofluran gefunden [57,60].…”
Section: Introductionunclassified
“…In the mature organism, surgery has been shown to result in the suppression of NK cytotoxic activity in both humans [19,20] and animals [21,22]. Studies in mature animals have shown that surgery and other stressors reduce host resistance against metastasis by suppressing NK activity [21,[23][24][25][26], and stressinduced immune suppression has been suggested to contribute to the deleterious effects of surgical intervention on metastatic development [26].…”
Section: Introductionmentioning
confidence: 99%